Bandgap Engineering in OH‐Functionalized Silicon Nanocrystals: Interplay between Surface Functionalization and Quantum Confinement. (2nd August 2017) - Bürkle, Marius; Lozac'h, Mickaël; McDonald, Calum; Mariotti, Davide; Matsubara, Koji; Švrček, Vladimir
Abstract : In this work, a systematic first‐principles study of the quasi‐band structure of silicon nanocrystals (Si‐NCs) is provided, focusing on bandgap engineering by combining quantum confinement of the electronic states with OH surface‐functionalization. A mapping between the bandgap, Si‐NC diameter, and the degree of hydroxide coverage is provided, which can be used as a guideline for bandgap engineering. Complementary to first‐principles calculations, the photoluminescence (PL) wavelength of Si‐NCs in the quantum‐confinement regime is measured with well‐defined diameters between 1 and 4 nm. The Si‐NCs are prepared by means of a microplasma technique, which allows a surfactant‐free engineering of the Si‐NCs surface with OH groups. The microplasma treatment technique allows us to gradually change the degree of OH coverage, enabling us, in turn, to gradually shift the emitted light in the PL spectra by up to 100 nm to longer wavelengths. The first‐principles calculations are consistent with the experimentally observed dependence of the wavelengths on the OH coverage and show that the PL redshift is determined by the charge transfer between the Si‐NC and the functional groups, while on the other hand surface strain plays only a minor part. Abstract : A systematic way to engineer the bandgap of silicon nanocrystals by means of variable particle‐size and surface chemistry is introduced, where the surface chemistry is tailored by replacing H with OH. This is a simple yet powerful approach allowing to gradually tune the bandgap and to control optical properties, e.g., for applications in third‐generation solar cells.